THE GENESIS OF THE CRIMINAL'S PERSONALITY IN THE DIGITAL AGE (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The aim of this research is to analyze and understand the issues of a criminal's personality in the digital age to promote more effective crime prevention. It aims to analyze contemporary problems and challenges related to the identification of criminal individuals in the context of digital technologies. This research can contribute to criminology, sociology, and psychology by elucidating how the use of such technology can impact the fight against criminally inclined individuals through digital identification means. The tasks of the research involve analyzing the influence of the digital era on the genesis of a criminal's personality in the mechanism of criminal acts. The novelty of the research is linked to the concentration of the crime prevention system on exploring the mechanism of forming a criminal's personality in the digital age. The research approach will enable a deeper understanding of how the digital era influences the potential formation of personality. The research will employ methods such as theoretical methods based on the analysis of scientific research and publications, exploration of criminal identification processes in the field of digital technology, and the use of content analysis to assess the effectiveness of applied identification technologies. The author assumes that digital technologies provide powerful tools for identifying criminals but are associated with several legal issues. A balance between the use of digital technology, the effectiveness of appropriate methods, and respect for human rights and freedoms is crucial. Recommendations will be provided in the conclusion, focusing on improving legal regulations for identification technologies, considering the identified problems. An analysis of the effectiveness of existing methods and technologies will also be conducted, addressing ethical and legal issues. A special training program and implementation procedure for law enforcement agencies on the ethical and legal aspects of using digital identification methods will be proposed.